Effect of different ratio and sintering temperature for the immobilization of simulated zinc sludge in aluminium rich ceramics - Nur shahirah; Azhari, Azra Syazwani; Hussainy, Husna Nadira; Abdul Aziz, Nor Nazumi (Multidisciplinary Applied Research and Innovation, 2020)
The aimed of this study is to investigate the formation of new compound between the aluminium oxide, Al2O3 and zinc oxide, ZnO that lead to the immobilization of this compound in fired clay brick. Al2O3 is known to have the second highest amount of clay precursor in brick manufacturing. The Zn is chosen because it is one of the most hazardous metals which is not biodegradable, that are commonly found in industrial waste. A research has been conducted and able to stabilize the heavy metals with well conducted thermal treatment schemes. The experiment showed that the stabilization of Zn only appear when it is exposed at high temperature; 1000°C and high ratio; 1:1 resulting in high formation of ZnAl2O4. The incorporation of heavy metal into clay precursor through thermal treatment process seen to help in clay dependency and heavy metal pollution. Thus, this findings may be a beneficial guide to immobilize hazardous metal in crystal form and to be used as the raw material in the development of ceramic products since it is not harmful to environment and humankind to be used as building material.